Last night was fun : a novel - Michelle, Holly (Avon, an imprint of HarperCollinsPublishers, 2025)
"You've Got Mail meets The Hating Game-vying for a promotion against a bitter rival as the only female data analyst for a baseball team, Emmy finds solace in the text-flirting relationship that started as a wrong number exchange-unaware that the man she's texting is the one she's fighting for the promotion"--